How qPCR complements the WHO roadmap (2021–2030) for soil-transmitted helminths. Issue 8 (August 2021) - Papaiakovou, Marina; Littlewood, D. Timothy J.; Gasser, Robin B.; Anderson, Roy M.
Abstract : Complementing the launch of the World Health Organization (WHO) roadmap (2021–2030) we explore key elements needing attention before recruitment of qPCR as the main diagnostics tool to confirm reduction or elimination of soil-transmitted helminth (STH) transmission in both control and elimination programmes. Given the performance limitations of conventional methods, a proposed harmonised qPCR will provide a diagnostic tool, with the sensitivity and specificity required to monitor low-intensity infections, following mass drug administration (MDA). Technical and logistical challenges associated with introducing qPCR as a stand-alone tool are highlighted, and a decision-making scheme on how qPCR can support surveillance, resistance detection, and elimination is presented. An accurate point-of-care (POC) diagnostic test needs to be developed to support STH control in the field, and STH biorepositories need to be established and maintained to ensure that reference materials are available for research and validation. Highlights: Sensitivity, specificity, and the potential for multiplexing are some of the traits that keep qPCR at the forefront of diagnostic tools to support the 2021–2030 World Health Organization (WHO) roadmap. Reproducible qPCR practices, through in-built quality-assessment schemes and harmonised workflows, can underpin effective control in the absence of complementary copro-diagnostic methods. The biological and clinical relevance of results from qPCR are yet to be agreed upon. 'Presence/absence' should be carefully evaluated in low-prevalence settings to confirm that presence equals infection. qPCR can be tailored to complement surveillance and elimination strategies and support programme assessments and screening for resistance. Soil-transmitted helminth (STH) biorepositories (stool and DNA) from different geographical locations are needed to validate any newly developed diagnostics and ensure uniformity in performance amongst laboratories.